Dissipation of Hysteretic Energy in Base Isolated Structure. (1996) - Jangid, R.S.; Datta, T.K.
Abstract : Dissipation of hysteretic energy in the isolator of the base isolated structure under seismic excitation is investigated. The hysteretic force-deformation characteristics of the base isolator is specified by a nonlinear differential equation. The parameters of the equation can be adjusted to obtain various types of hysteretic models of the isolator including the elastoplastic type. The variation of hysteretic energy dissipated in the isolators is obtained for both harmonic and El-Centro 1940 earthquake ground motion for a set of important parameters. They include time period of superstructure, ratio of superstructure mass to base mass, level of yield strength of the isolator, post- to preyielding stiffness ratio, and the ratio of harmonic excitation frequency to base isolation frequency. It is shown that the dissipation of hysteretic energy in the isolator is significantly influenced by the above parameters.